Performance analysis of RIP, IGRP, EIGRP and OSPF-based network - Lye, Yam Meng. (2008)
This thesis provides the performance analysis of interior gateway protocols (Routing Information Protocol (RIP), Interior Gateway Routing Protocol (IGRP), Enhanced Interior Gateway Routing Protocol (EIGRP) and Open Shortest Path First (OSPF) by evaluating each routing protocol behavior and characteristic. The theoretical routing protocol functions, behavior and characteristics are studied and analyzed in this thesis.